Can opener - Mohd Hafez, Saat (2009)
This report will present about the can opener. The can opener is a device that will use to open the metal can especially for the sardine can, food can and also milk can. Most cans have identical and parallel round tops and bottoms with vertical sides. The idea of fabricate of this can opener based on student creativity. This can opener will be fabricating with have the frame body that will combine with clamper to clamp the tin can. In the fabrication, there are many process involve to develop the product such as drilling, grinding, joining, measuring, gathering material, cutting material, and finishing process. This project is about design and fabricates a new product of can opener that has safety to user and more stable when it cut the metal can. Material are be used to fabrication of the can opener is a mild steel and stainless steel. In this report also that will more focus about the fabrication of this can opener.